GE_GERICHTE A/729/2021 vom 18. Oktober 2021 - GE Cour de justice (2021)
DÉDUCTION DU REVENU(DROIT FISCAL);FRAIS SUPPLÉMENTAIRES CAUSÉS PAR L'INVALIDITÉ;INVALIDITÉ(INFIRMITÉ) | LIFD.33.al1.lethbis; LIPP.32.letc; LIFD.34.leta; LIPP.38.leta